2020
DOI: 10.3390/cancers12030727
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Mechanisms of Tumor PD-L1 Expression by Natural Bioactive Gallic Acid in Non-Small-Cell Lung Cancer (NSCLC) Cells

Abstract: Non-small-cell lung cancer (NSCLC) is the most common lung cancer subtype and accounts for more than 80% of all lung cancer cases. Epidermal growth factor receptor (EGFR) phosphorylation by binding growth factors such as EGF activates downstream prooncogenic signaling pathways including KRAS-ERK, JAK-STAT, and PI3K-AKT. These pathways promote the tumor progression of NSCLC by inducing uncontrolled cell cycle, proliferation, migration, and programmed death-ligand 1 (PD-L1) expression. New cytotoxic drugs have f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 82 publications
0
39
1
Order By: Relevance
“…The hallmarks of cancer mainly consist of the lost ability to induce apoptosis and the induction of angiogenesis, resulting in metastasis via tumor cell migration, invasion, and EMT. A drug that can inhibit these processes in a cancer cell will be suitable for anticancer studies [ 46 ]. We found that UA can induce cell death in A549 and H460 cells, which are both considered metastatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The hallmarks of cancer mainly consist of the lost ability to induce apoptosis and the induction of angiogenesis, resulting in metastasis via tumor cell migration, invasion, and EMT. A drug that can inhibit these processes in a cancer cell will be suitable for anticancer studies [ 46 ]. We found that UA can induce cell death in A549 and H460 cells, which are both considered metastatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Many natural compounds (e.g. Triptolide(20), Galic acid(21) and Resveratrol(22)) were also able to inhibit the expression of PD-L1 in cancer cells through various mechanisms. Like metformin, these compounds are multifunctional rather than just affecting the expression of PD-L1.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR can contribute to transformation of cellular phenotypes that enable tumor cell growth and survival [ 32 , 33 ]. EGFR signaling can also induce immune activation by activating p53 signaling, which thereby inhibits PD-L1 expression [ 34 ]. Steroid receptor coactivator (Src) is an intracellular tyrosine kinase that takes part in tumorigenesis via signaling from EGFR through association with focal adhesion kinase (FAK) [ 35 ].…”
Section: Introductionmentioning
confidence: 99%